2014
DOI: 10.1137/100803869
|View full text |Cite
|
Sign up to set email alerts
|

Packing Triangles in Weighted Graphs

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(87 citation statements)
references
References 7 publications
0
87
0
Order By: Relevance
“…• If t overlaps with exactly one triangle ψ ∈ V, we say that t is singly-attached 3 to ψ, and the unique edge in E(t) ∩ E(ψ) is called a base-edge. The vertex anchor(t) := V(t) \ V(ψ) 4 is called the anchoring vertex of t.…”
Section: The Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…• If t overlaps with exactly one triangle ψ ∈ V, we say that t is singly-attached 3 to ψ, and the unique edge in E(t) ∩ E(ψ) is called a base-edge. The vertex anchor(t) := V(t) \ V(ψ) 4 is called the anchoring vertex of t.…”
Section: The Setupmentioning
confidence: 99%
“…For each solution triangle ψ ∈ V, denote the conflict list of ψ by C L(ψ) which contains triangles in T − V whose edges overlap with ψ. We naturally partition C L(ψ) into C L sin (ψ) ∪ C L dou (ψ) ∪ 3 The notion of "attachment" we use here is motivated by the view that triangles in V are the "skeleton" of the graph, and the rest of the graphs are "attachments" hanging around the skeleton. 4 For singleton sets, we abuse notations a bit by interchangeably using e and {e}.…”
Section: Types Of Solution Trianglesmentioning
confidence: 99%
See 1 more Smart Citation
“…The best general upper bound on τ (G) in terms of ν(G) is due to Haxell [12], who showed that τ (G) ≤ 2.87ν(G) for all graphs G. Tuza's Conjecture has been studied by many authors, who proved the conjecture for special classes of graphs [14,18,23,25,26] or studied various fractional relaxations of the conjecture [6,13,15,18].…”
mentioning
confidence: 99%
“…A similar idea, restricted to k = 1, appears in [15] and [6], where H is taken to be a triangle-free Ramsey graph with small independence number, and graphs of the form I 1 ∨ H are used as sharpness examples for upper bounds on τ (G).…”
mentioning
confidence: 99%